2018
DOI: 10.1097/ico.0000000000001790
|View full text |Cite
|
Sign up to set email alerts
|

Capnocytophaga Keratitis: Clinical Presentation and Use of Metagenomic Deep Sequencing for Diagnosis

Abstract: Purpose: To report our experience with two cases of Capnocytophaga keratitis. Methods: Retrospective case reports. We present the clinical presentation, diagnosis and treatment strategies of two patients who presented with Capnocytophaga keratitis. Results: Both patients had risk factors including systemic immune compromise and ocular trauma. Both patients had robust inflammatory keratitis with necrosis. Case 1 demonstrates identification of Capnocytophaga with traditional microbiologic techniques. Case 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…So far, NGS has demonstrated promise in augmenting clinical microbiology and public health laboratory practice (Gwinn et al, 2019 ), and its applicability is now gradually gaining traction in the field of IK (Ung et al, 2020 ). Owing to its high sensitivity and specificity, studies have shown that NGS is able to yield positive results in culture-negative IK cases (where the infectious bioburden is usually low or the infection is caused by atypical organisms or fungi), with a quick turnaround time (Seitzman et al, 2019a , b ). It can sequence all types of organisms, including bacteria, fungi, viruses, and parasites, an advantage that is particularly valuable for IK where polymicrobial infection is relatively common.…”
Section: Potential Solutions For Improving Diagnostic Performancementioning
confidence: 99%
“…So far, NGS has demonstrated promise in augmenting clinical microbiology and public health laboratory practice (Gwinn et al, 2019 ), and its applicability is now gradually gaining traction in the field of IK (Ung et al, 2020 ). Owing to its high sensitivity and specificity, studies have shown that NGS is able to yield positive results in culture-negative IK cases (where the infectious bioburden is usually low or the infection is caused by atypical organisms or fungi), with a quick turnaround time (Seitzman et al, 2019a , b ). It can sequence all types of organisms, including bacteria, fungi, viruses, and parasites, an advantage that is particularly valuable for IK where polymicrobial infection is relatively common.…”
Section: Potential Solutions For Improving Diagnostic Performancementioning
confidence: 99%
“…Seitzman et al [ 166 ] compared the diagnostic efficacy of MDS with conventional culture and viral PCR in patients with IK and demonstrated that MDS was able to unveil all range of causative microorganisms (including bacteria, fungi, Acanthamoeba and herpes simplex virus) in one single assay. The versatility of MDS in diagnosing all types of IK, including culture-negative cases, has been demonstrated in other studies [ [167] , [168] , [169] , [170] ].…”
Section: Future Directionsmentioning
confidence: 65%
“…To date, only a few studies have evaluated the potential utility of MDS for diagnosing IK [ [166] , [167] , [168] , [169] ]. Seitzman et al [ 166 ] compared the diagnostic efficacy of MDS with conventional culture and viral PCR in patients with IK and demonstrated that MDS was able to unveil all range of causative microorganisms (including bacteria, fungi, Acanthamoeba and herpes simplex virus) in one single assay.…”
Section: Future Directionsmentioning
confidence: 99%
“…Like our presented case, patients with Capnocytophaga keratitis report frequent and close interactions with dogs (e.g. face licking) [ 17 ]. Patients susceptible to Capnocytophaga keratitis are often immunocompromised—for example, status post bone marrow transplant, or rituximab infusions.…”
Section: Discussionmentioning
confidence: 88%
“…veterinarians) are also at risk [ 7 ]. Topical clindamycin has been used with good clinical results in some patients [ 7 , 16 , 17 ]. Some clinicians have also used oral clindamycin to achieve higher levels of antibiotics in the anterior chamber and deeper layers of the cornea where Capnocytophaga resides.…”
Section: Discussionmentioning
confidence: 99%